2019
DOI: 10.1007/s13592-019-00721-9
|View full text |Cite
|
Sign up to set email alerts
|

Varroa destructor reproduction and cell re-capping in mite-resistant Apis mellifera populations

Abstract: Globalization has facilitated the spread of emerging pests such as the Varroa destructor mite, resulting in the near global distribution of the pest. In South African and Brazilian honey bees, mite-resistant colonies appeared within a decade; in Europe, mite-resistant colonies are rare, but several of these exhibited high levels of "recapping" behavior. We studied recapping in Varroa-naïve (UK/Australia) and Varroa-resistant (South Africa and Brazil) populations and found very low and very high levels, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 51 publications
4
82
2
1
Order By: Relevance
“…This behavior, a product of rapid evolution, avoids the cost of losing brood. These results were confirmed by Martin et al [ 73 ] when comparing cell recapping in mite-resistant honey bees from Brazil and Africa ( A. m. scutellata ) with “mite-naive” honey bees from the United Kingdom and Australia.…”
Section: Discussionsupporting
confidence: 73%
“…This behavior, a product of rapid evolution, avoids the cost of losing brood. These results were confirmed by Martin et al [ 73 ] when comparing cell recapping in mite-resistant honey bees from Brazil and Africa ( A. m. scutellata ) with “mite-naive” honey bees from the United Kingdom and Australia.…”
Section: Discussionsupporting
confidence: 73%
“…larvae. This activity suggests that a behavioral defense which predated Varroa is now being used as a primary tool of social immunity against the mite (Villegas and Villa 2006;Martin et al 2019). The activity also is notable because it apparently represents a response only to stimuli produced by the pupa.…”
Section: Mechanisms Of Detection Of D I S E a S E D A N D V A R R O Amentioning
confidence: 99%
“…Colonies that are apparently resistant to Varroa display high frequencies of cell recapping; that is, the wax capping over a pupa is opened, then recapped with wax (Boecking and Spivak 1999;Aumeier et al 2000;Harris et al 2012;Martin et al 2019). Recapping by the bees is evident when the cell capping is experimentally removed and inspected from underneath; if it has been recapped, there is a circular area with no silk lining.…”
Section: Recappingmentioning
confidence: 99%
“…Later, in a comparison of Africanised and A. m. carnica colonies with regards to VSH, it was determined that three to seven days after the initial artificial infestation, the absence of only the introduced mite was more common than the removal of both the mite and pupae (Aumeier and Rosenkranz, 2001;Aumeier et al, 2000). Comparable findings were later obtained in A. m. scutellata (Cheruiyot et al, 2018), and high recapping rates were identified in naturally surviving A. m. capensis and Africanised honey bees (Martin et al, 2019b). As the cells were experimentally sealed after infestation, it can be hypothesised that they were opened by adult workers, which induced the exit of the mite, before later being recapped.…”
Section: Uncapping-recappingmentioning
confidence: 99%